Forecasting The Manpower Requirement in Vietnamese Tertiary Institutions - CHIA-NAN, Wang; TY, Nguyen Nhu (Asian Journal of Empirical Research, 2013)
In Vietnam, the number of students has risen so fast since reform and opening-up; whereas, the faculties are not enough to be sufficient to that raising. In fact, the Bachelors are outnumbered in many Vietnamese universities. Thus, the problem is how to prepare and to reach the high qualified teaching/learning and faculty to adapt with the rising numbers of students in recent years and next years on. In addition, this research is to do analyses and get prediction values of students and faculties in all Vietnamese universities for the future by taking the statistics provided by the Ministry of Vietnamese Education and Training from 1999 to 2011 and adapting Grey Model to forecast. This study also analyses on the trending of the faculty and students to get valuable results which are accurate by applying the Mean Absolute Percentage Error (MAPE) showing low range errors. After that, this study can provide the Ministry of Vietnamese Education and Training (MOET) a good method and results to plan the education policies and resources allocation in the future.